The Effect of Transactional Leadership and Punishment on Employee Performance with Motivation as an Intervening Variable for the Management Body Revenue Finance and Regional Assets of Binjai City - Nadratul Firda; Kiki Farida Ferine (International Journal of Economics, Management and Accounting (IJEMA), 2023)
This study aims to analyze the effect of transactional leadership and punishment on employee performance with motivation as an intervening variable. This type of research uses associative quantitative research, and this research was conducted at the Office of Regional Income and Asset Financial Management Agency, Binjai City. The research population consists of 173 employees. The sampling technique used the Slovin formula and the sample used was 121 employees. The data collection used a questionnaire. The research model used is Path Analysis and the measurement tool is Smart PLS version 3.3.3. The results of this study are that Transactional Leadership has a positive and significant effect on Employee Performance Transactional Leadership has a positive and significant effect on Motivation. Motivation has a positive and significant effect on employee performance. Punishment has a positive and significant effect on employee performance. Punishment has a positive and significant effect on motivation. Transactional Leadership influences Employee Performance through Motivation in a positive and significant way. Punishment influences Employee Performance through Positive and Significant Motivation.